Pengaruh Kemudaha Penggunaan dan Manfaat Penggunaan Terhadap Minat Menggunakan Quick Response Code Indonesian Standard (QRIS) Pada Pedagang di Pantai Penimbangan - Jodi, Kadek Agus Setiawan; Irwansyah, M. Rudi (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This research aims to determine "The Influence of Ease of Use and Benefits of Use on Interest in Using the Quick Response Code Indonesian Standard (QRIS) among Traders on Penimbangan Beach" either partially or simultaneously. This type of research uses a quantitative approach. The population used is all traders on Penimbangan Beach. The sample used in this research was a saturated sample or by making the entire population into a sample, namely 87 traders. The data sources used are secondary and primary data sources. Data collection methods in this research are observation, interviews and also a questionnaire method using a Likert scale. The analysis technique used in this research is the multiple linear regression analysis technique with partial (t test) and simultaneous (F test) hypothesis testing. The results of this research show that: (1) ease of use has a positive and significant effect on interest in using QRIS at Penimbangan Beach, (2) benefits of use have a positive and significant effect on interest in using QRIS at Penimbangan Beach, and (3) ease of use and overall benefits of use. simultaneously has a positive and significant effect on interest in using QRIS at Penimbangan Beach.